PELATIHAN MICROSOFT EXCEL DALAM MENINGKATKAN KEMAMPUAN SANTRI-SANTRI DI PONDOK PESANTREN TAHFIZH AL-QUR'AN DAARUL HIKMAH CIPUTAT, KOTA TANGERANG SELATAN, BANTEN - Nurhayati; Adam Muiz; Eka Yuni Titik Artaningsih (Abdi Jurnal Publikasi, 2025)
This Community Service Activity was held to provide understanding to the female and female students of the Tahfiz Daarul Hikmah Ciputat Islamic Boarding School about the importance of using Microsoft Office in everyday life, especially Microsoft Excel to facilitate various activities such as making reports, etc. For this reason, the Pamulang University Community Service team provides outreach regarding what Microsoft Office is, especially Microsoft Excel and how to apply basic Microsoft Excel formulas. This activity is carried out using the workshop or seminar method, where the method is carried out in several forms of activities, such as lectures as well as presenting material regarding the basics of Microsoft Excel, and how to apply it in everyday life to make work or school assignments easier by using PowerPoint and practice. In fact, he was directly accompanied by lecturers and fellow Pamulang University students. With this method, students have more inspiration and knowledge about what and how to use Microsoft Excel. This Community Service activity went smoothly, on time, and as expected. This was proven by the participants' active participation in the entire event process and the question and answer process given.